Wittgenstein and the method of analysis by propositional types in On Certainty - Chica Pérez, Víctor Hugo (Estudios de Filosofía, 2015)
My purpose in this article is to provide a reconstruction of the mechanics of philosophical analysis that Wittgenstein carried out in “On Certainty”. I will show that this analysis is based, specifically, on an appeal to a wide propositional typology that serves to evaluate and diagnose Moore’s propositions. To this end, I shall first explain how common readings of the methodological issues in “On Certainty” fail. Secondly, I focus on the mechanics of analysis found in paragraphs 1-65, specifically the analysis of three sentences: “There are physical objects”, “I know that there is a hand here” and “here the mistake is impossible”. Thirdly, I proceed to identify different stages of the method and justify in what sense the strategic core of such research is the table of propositional typologies.